2018
DOI: 10.30831/akukeg.364483
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmeni Adaylarının Matematik Öğretimi Kaygıları ve Matematik Öğretimi Yeterlikleri

Abstract: The purpose of this study is to examine the classroom teacher candidates' mathematics teaching concerns and mathematics teaching competencies according to various variables. The sampling of the survey was made up of 222 classroom teacher candidates who study at the education department of a state university. As datagathering tools; "Mathematics Teaching Anxiety Scale" and "Mathematics Teaching Efficacy Scale" have been used. As a result of this study, mathematics teaching anxieties of prospective teachers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
1
3
0
11
Order By: Relevance
“…There are also studies in the literature in which mathematics and mathematics teaching anxiety do not differ according to gender (Cooper & Robinson, 1991;Brush, 1978;Sirmaci, 2007;Townsend, Moore, Tuck & Wilton, 1998). Deringöl (2018) concluded that the anxiety level of women is lower than men in the anxiety sub-dimension of mathematics education anxiety and field knowledge. There are also studies in the literature where the anxiety of mathematics and mathematics teaching does not differ by gender (Tatar, Zengin & Kağızmanlı, 2016, Küçük Demir et al, 2016Cooper & Robinson, 1991, Brush, 1978, Sırmacı, 2007, Townsend, Moore, Tuck & Wilton , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies in the literature in which mathematics and mathematics teaching anxiety do not differ according to gender (Cooper & Robinson, 1991;Brush, 1978;Sirmaci, 2007;Townsend, Moore, Tuck & Wilton, 1998). Deringöl (2018) concluded that the anxiety level of women is lower than men in the anxiety sub-dimension of mathematics education anxiety and field knowledge. There are also studies in the literature where the anxiety of mathematics and mathematics teaching does not differ by gender (Tatar, Zengin & Kağızmanlı, 2016, Küçük Demir et al, 2016Cooper & Robinson, 1991, Brush, 1978, Sırmacı, 2007, Townsend, Moore, Tuck & Wilton , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Buna göre kadın ve erkek öğrencilerin matematik öğretimine ilişkin benzer kaygı düzeylerine sahip oldukları söylenebilir. Bu sonuç alanda yapılan diğer benzer çalışma sonuçları ile de benzerlik göstermektedir (Demir vd., 2016;Deringöl, 2018;Peker & Ertekin, 2011;Peker vd., 2010;Tatar vd., 2016). Örneğin; Peker ve Ertekin (2011) çalışmalarında matematik öğretmeni adaylarının matematik öğretimine yönelik kaygı düzeyleri ve matematik kaygı seviyeleri arasında ilişkiyi araştırmıştır.…”
Section: Tartişma Ve Sonuçunclassified
“…Örneğin; Peker ve Ertekin (2011) çalışmalarında matematik öğretmeni adaylarının matematik öğretimine yönelik kaygı düzeyleri ve matematik kaygı seviyeleri arasında ilişkiyi araştırmıştır. Araştırmanın sonucunda matematik öğretmeni adaylarının cinsiyet değişkenine göre matematik öğretimine yönelik kaygılarında anlamlı farklılık olmadığı sonucuna ulaşılmıştır Ancak bu araştırma bulguları ile benzerlik göstermeyen çalışmalara da rastlamak mümkündür (Çenberi, 2019;Deringöl, 2018;Doruk & Kaplan, 2013). Örnek Doruk ve Kaplan (2013) çalışmasında erkek öğrencilerin matematiğe ilişkin kaygılarının kadın öğrencilere göre daha düşük olduğu sonucuna ulaşmıştır.…”
Section: Tartişma Ve Sonuçunclassified
See 2 more Smart Citations